2018
DOI: 10.1093/jhps/hny025
|View full text |Cite
|
Sign up to set email alerts
|

Proximal iliotibial band thickness as a cause for recalcitrant greater trochanteric pain syndrome

Abstract: To investigate iliotibial band (ITB) diameter thickness at the greater trochanter in patients requiring iliotibial band release who have failed conservative modalities, in comparison to an asymptomatic patient population. A total of 68 subjects were selected to be reviewed using T2 axial plane MRI. The ITB diameter thickness was measured in 34 subjects who underwent surgical ITB release, and compared with a match-paired asymptomatic hip cohort consisting of 34 subjects. ITB diameter thickness was measured at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…Studies have shown that the ITB thickness varies depending on the location from its origin at the anterior superior iliac spine to its insertion at the Gerdy tubercle 25 . In a recent study, Khoury et al 26 reported the mean ITB thickness at the peritrochanteric area on magnetic resonance imaging in an asymptomatic population to be 3.8 mm. However, the distance between the jaws of the Kemis knife blade is 3.1 mm; therefore, a dedicated disposable knife with increased sharpness and size would be ideal to cut the ITB with improved accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the ITB thickness varies depending on the location from its origin at the anterior superior iliac spine to its insertion at the Gerdy tubercle 25 . In a recent study, Khoury et al 26 reported the mean ITB thickness at the peritrochanteric area on magnetic resonance imaging in an asymptomatic population to be 3.8 mm. However, the distance between the jaws of the Kemis knife blade is 3.1 mm; therefore, a dedicated disposable knife with increased sharpness and size would be ideal to cut the ITB with improved accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison between symptomatic (painful) and asymptomatic snapping, the following soft-tissue related parameters were compared between groups: presence of trochanteric bursitis or gluteal tendinopathy and ITB (Iliotibial band) thickness [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…The measurement location was considered as the region of greatest thickness between the most proximal images of the greater trochanter to the most proximal sequence showing the lesser trochanter. [ 9 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Although the iliotibial tract is most recognized for its role in lateral knee pain related to friction (most commonly in runners and patients with low body mass index, causing relative paucity of fat padding between the ITB, the lateral femoral cortex, and fibula), similar symptoms were described proximally as the ITB crosses over the greater trochanter. 64 This is seen in certain sports requiring repetitive abduction, flexion, and external rotation during knee extension (such as running, swimming, gymnastics, ballet, and soccer). ITB snapping commonly presents in young and physically active patients.…”
Section: Snapping Hip From Extra-articular Originmentioning
confidence: 99%